Performance of reinforced soil structures proceedings of the International Reinforced Soil Conference organized by the British Geotechnical Society and held in Glasgow on 10-12 September 1990 - McGown, Alan, 1941-; Yeo, Khen; Andrawes, K. Z. (Thomas Telford, 1991)
This volume discusses all aspects of the performance of reinforced soil structures and offers innovative design solutions to ensure the successful behaviour of these structures. It analyses the theory, design and construction influences on the performance and reinforced soil structures providing comparative state-of-the-art technical data.